Perspectives of Facial Plastic Surgeons on Opioid Dependence in Rhinoplasty Patients - Levin, Marc; Roskies, Michael G.; Asaria, Jamil (Facial Plastic Surgery, 2019)
Understanding the perspectives and opinions of facial plastic surgeons on opioid dependence is critical in a national epidemic of opioid overuse. Findings may encourage surgeon education so that facial plastic surgeons may be able to judiciously prescribe opioids, improving patient outcomes and reducing healthcare opioid-related spending. The objective of this study is to understand facial plastic surgeons' perspectives on opioid dependence in rhinoplasty patients. A key secondary objective was to quantify facial plastic surgeons' opioid prescribing patterns. This was a prospective survey study. A nine-question survey was sent to all members of the American Academy of Facial Plastic and Reconstructive Surgery in July of 2018, and analysis of the data was completed in August of 2018. The primary study outcome measurement was surgeon perspectives on opioid dependence. This was measured by an online survey. A total of 164 facial plastic surgeons responded to the survey (response rate: 6.6%). The majority were experienced surgeons in practice for more than 10 years (61.96%) who perform less than five rhinoplasties per week (84.15%). Of the facial plastic surgeons, 89.51% prescribe some variation of opioids following rhinoplasty. Most surgeons believe that opioid dependence is not a problem in rhinoplasty patients (86.96%), but that it is a problem among surgical patients in general (61.11%). The majority (52.45%) of surgeons prescribe between 11 and 25 tablets of opioids following rhinoplasty, with 25.17% of surgeons prescribing > 25 tablets of opioids. Facial plastic surgeons do not believe opioid dependence to be a problem among rhinoplasty patients. Resultantly, many facial plastic surgeons can prescribe more than 25 tables of opioids following rhinoplasty. The findings suggest that facial plastic surgeons may require further education and complete more research regarding opioid dependence among the rhinoplasty population. Additionally, the findings are important for health policy in that they encourage the creation of rhinoplasty specific opioid prescription guidelines.
Keywords: rhinoplasty; postoperative pain management; clinical decision-making; opioids; surgeon perspectives